Factors and challenges influencing money laundering investigation outcome among the law enforcement agencies in Malaysia / Salwa Zolkaflil - Zolkaflil, Salwa (2020)
Money laundering is a global issue which if not accordingly mitigated will result in negative implication towards global economy and a country’s reputation. Due to such risks, penalty for money laundering offence, which includes both fines and imprisonment is stiff. In addition, there are special confiscation provisions in the Anti-Money Laundering Act 2001 to freeze, seize or forfeit illegal-gotten gains of perpetrators. Regulators and law enforcement agencies are also treating money laundering as a priority issue to be effectively mitigated across the nation. Despite the increased number of reported money laundering cases in Malaysia, investigation outcome either in the forms of prosecution, conviction or confiscation remains low and ineffective in deterring money laundering activities. Using the Rational Choice Theory, this study aims to address the issues by looking into the reasons behind the unfavourable investigation outcome. To address the issues, data collection was done in three stages using the mixed method approach. Stage One: comprises content analysis of the Mutual Evaluation Reports (MER) which are based on the member country’s compliance against international anti money laundering standards developed by the Financial Action Task Force (FATF). Stage Two: data collection involves three focus group interviews, face-to-face interviews and fact-finding survey with money laundering investigating officers of selected law enforcement agencies in Malaysia. The Stage Three: data collection includes face-to-face interviews with other senior officers who are also involved either directly or indirectly in the money laundering investigation loop. The current study on money laundering investigation uses the phenomenology approach for data collection and analysis. Specifically, the study focuses on the “first-person point of view” experiences of investigating officers and anti-money laundering experts. The aim is to have in-depth understanding on both factors and challenges faced by investigating officers in conducting money laundering investigation which had resulted in both low number of money laundering prosecution, conviction and confiscation. The interviews were transcribed and analysed using NVIVO Software while the fact-findings survey was analysed using Statistical Package for the Social Sciences (SPSS) and Partial Least Squares (PLS) of Structural Equation Modelling. The findings demonstrate that money laundering investigation outcome is influenced by three factors which are namely cost-benefit analysis, individual belief, and organisational context factor. Further, the investigation outcome is also influenced by the availability of resources (financial, human and time) and legislative support (prosecuting power). Due to these limitations, the investigating officers have higher preference to proceed with non-prosecution (asset confiscation) instead of prosecution (criminal action) which helps to produce a satisfactory investigation outcome. This is in tandem with the Rational Bounded Theory, which posits limitations influence decision making, hence implicates the outcome of the money laundering investigation. The findings of the study provide significant contributions in confirming the theoretical foundations underpinning this research as well as adds value to the existing body of knowledge on money laundering. Extending the study on behavioural issues to a vastly different landscape helps to set a new branch of research in the related areas.